Once Upon a Monbeast... - Fritch, Charles E., 1927-2012 (Salt Lake City, UT : Project Gutenberg, 2021)
"Once Upon a Monbeast..." by Charles E. Fritch is a science fiction short story written during the early 1950s. The narrative revolves around the struggles of a fledgling science-fiction writer who encounters the whimsical and possibly dangerous consequences of his own imagination when he brings a creature from his writing to reality. The story blends humor and a hint of existentialism as it explores the relationship between creativity and the potential perils that come with it. The plot follows an unnamed protagonist who is initially disheartened by the harsh criticism from the established writer Donald MacDonald. Despite feeling demoralized, he continues to write and eventually receives a publication acceptance, which excites him. However, when he creates a story about a creature called the monbeast, that very creature unexpectedly appears in his life, leading to bizarre and humorous interactions. The monbeast reveals its true nature as a product of the author's imagination and emphasizes that now the responsibility lies with the writer to create more compelling beings, hinting at the inescapable bond between a creator and their creations. The story ends on an eerie note, suggesting that such creatures might be lurking just beyond the veil of reality, leaving readers to ponder the implications of their creative endeavors. (This is an automatically generated summary.)
Release date is 2021-07-05
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Science fiction -- Authorship -- Fiction